Penerapan Teknologi Informasi untuk Mendorong Kemandirian Desa di Era Digital - Muhammad Ridho (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
Village independence is one of the priorities in national development, especially in improving the welfare of rural communities. Information technology (IT) has an important role in speeding up this process, especially in the current digital era. This research aims to implement the application of information technology to encourage village independence, both in economic, administrative and social aspects. The method used is a case study in Village X, with a qualitative approach through interviews, observation and documentation analysis. The research results show that the application of IT, such as village information systems, local e-commerce, and web-based administration applications, is able to increase the efficiency of public services, expand market access for village products, and increase participation in village development communities. Thus, the correct application of IT can be an important pillar in realizing independent villages in the digital era.